Assassination nation [videorecording (DVD)] - Levinson, Sam, 1985-; Young, Odessa, 1990-; Nef, Hari; Waterhouse, Suki, 1992- (Universal, 2018)
After a malicious data hack exposes the secrets of the perpetually American town of Salem, chaos descends and four girls must fight to survive, while coping with the hack themselves.